MATHEMATICAL PROBLEM-SOLVING ABILITY OF STUDENTS IN TERMS OF ADVERSITY QUOTIENT AND SELF-EFFICACY - Charolina, Suci; Suhendra, Suhendra (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to analyze students' mathematical problem-solvingproblem-solving skills in SPLDV material in terms of adversity quotient and self-efficacy and provide recommendations for improving students' mathematical problem-solvingproblem-solving skills in schools with comparable backgrounds.Methodology – The research approach used is a qualitative approach with a case study method. The subjects of this study were three ninth-grade students selected based on the students' AQ and SE levels. The data collection technique used was triangulation. The test instrument for this study was a problem-solving ability test. The non-test instruments for this study were the AQ Questionnaire, SE Questionnaire, and interview guidelines. The techniques for examining data validity in qualitative research include testing credibility, transferability, dependability, and confirmability.Findings – The study found that students with a climber adversity quotient and high self-efficacy excel in mathematical problem-solving, fulfilling all four problem-solving indicators: understanding the problem, planning a strategy, implementing a solution, and re-examining the results. Students with a camper adversity quotient and high self-efficacy have good problem-solving skills but are not optimal, fulfilling three indicators. Students with a quitter adversity quotient and low self-efficacy tend to struggle, fulfilling only two indicators and often giving up. Contribution – The results of this study are expected to contribute to mathematics education by serving as a reference for research on students' mathematical problem-solving abilities about adversity quotient and self-efficacy.